2000
DOI: 10.1007/s002610000011
|View full text |Cite
|
Sign up to set email alerts
|

Update on digital image management and PACS

Abstract: Information technology is becoming a vital component of all health care enterprises, from managed care services to large hospital networks, that provides the basis of electronic patient records and hospital-wide information. The rationale behind such systems is deceptively simple: physicians want to sit down at a single workstation and call up all information, both clinical data and medical images, concerning a given patient. Picture archiving and communication systems (PACS) are responsible for solving the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…The test software developed for the present investigation bypasses those restrictions and allowed high numbers of measurements and repetitions with multiple concurrent clients and a high degree of synchronicity. To put our results in perspective, we assumed a reasonable waiting time for the display of images to be under 5 s, as has been reported in previous publications [3,5,17].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The test software developed for the present investigation bypasses those restrictions and allowed high numbers of measurements and repetitions with multiple concurrent clients and a high degree of synchronicity. To put our results in perspective, we assumed a reasonable waiting time for the display of images to be under 5 s, as has been reported in previous publications [3,5,17].…”
Section: Discussionmentioning
confidence: 97%
“…The importance of Web-based systems as a tool to provide hospital-wide distribution of radiological images [1,2,3] has increased over the past decade. Previous studies have examined the requirements of the personal computer (PC) client configuration, in order to identify combinations offering a suitable time-to-display (TTD) at a reasonable cost [4,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Moving towards an almost filmless hospital and an improved clinical work flow can only be achieved when this issue is solved [2,3]. Furthermore, recent studies have indicated that it could lead to considerable cost savings outside the Radiology Department [3]. Despite these facts, hospitalwide image distribution is still a challenge especially for larger hospitals.…”
Section: Introductionmentioning
confidence: 97%
“…Together with the increasing importance of hospital-wide image distribution as a prerequisite to achieve cost-savings and campus-wide process optimizations in picture archiving and communications systems (PACS) projects [1,2,3,4], there is an increasing demand for proper data on the performance and configuration of Web-based image distribution systems. A sufficient amount of information exists for the client performance and requirements [5,6,7], but the available material on the important server component is dedicated to the download properties [8].…”
Section: Introductionmentioning
confidence: 99%